Importance of suspended sediment (SPS) composition and grain size in the bioavailability of SPS-associated pyrene to Daphnia magna. (July 2016) - Xia, Xinghui; Zhang, Xiaotian; Zhou, Dong; Bao, Yimeng; Li, Husheng; Zhai, Yawei
Abstract: Hydrophobic organic compounds (HOCs) tend to associate with suspended sediment (SPS) in aquatic environments; the composition and grain size of SPS will affect the bioavailability of SPS-associated HOCs. However, the bioavailability of HOCs sorbed on SPS with different compositions and grain sizes is not well understood. In this work, passive dosing devices were made to control the freely dissolved concentration of pyrene, a typical HOC, in the exposure systems. The effect of pyrene associated with amorphous organic carbon (AOC), black carbon (BC), and minerals of SPS with grain sizes of 0–50 μm and 50–100 μm on the immobilization and enzymatic activities of Daphnia magna was investigated to quantify the bioavailability of pyrene sorbed on SPS with different grain sizes and compositions. The results showed that the contribution of AOC-, BC-, and mineral-associated pyrene to the total bioavailability of SPS-associated pyrene was approximately 50%–60%, 10%–29%, and 20%–30%, respectively. The bioavailable fraction of pyrene sorbed on the three components of SPS was ordered as AOC (22.4%–67.3%) > minerals (20.1%–46.0%) > BC (9.11%–16.8%), and the bioavailable fraction sorbed on SPS of 50–100 μm grain size was higher than those of 0–50 μm grain size. This is because the SPS grain size will affect the ingestion of SPS and the SPS composition will affect the desorption of SPS-associated pyrene in Daphnia magna . According to the results obtained in this study, a model has been developed to calculate the bioavailability of HOCs to aquatic organisms in natural waters considering both SPS grain size and composition. Graphical abstract: Highlights: Bioavailability of pyrene sorbed on AOC accounted for 50–60% of the total sorbed on SPS. Bioavailable fraction of pyrene sorbed on different SPS components was AOC > mineral > BC. Bioavailable fraction of pyrene sorbed on 50–100 μm SPS was higher than 0–50 μm SPS. A model was built to calculate the bioavailability of HOCs in natural waters with SPS. Both grain size and composition of SPS should be considered for HOC risk assessment. Abstract : The bioavailability of SPS-associated pyrene to Daphnia magna depends on both particulate grain size affecting SPS ingestion, and particulate composition affecting desorption of pyrene.